A Study of a Novel Synergy Definition for Ternary CB/CNT Composites Suggesting a Representative Model for CB and CNT - Yang, Guanda; Schubert, Dirk W.; Nilsson, Fritjof; Qu, Muchao; Redel, Michael (Macromolecular Theory and Simulations, 2020)
For polymer composites containing two types of conductive fillers, the electrical conductivity can be predicted with a ternary mixing equation. However, a slight deviation from the foreseen trend is recently observed for ternary polymethyl methacrylate (PMMA) nanocomposites containing carbon nanotubes (CNT) and carbon black (CB). In this study, the reason for the deviation is examined. Representative composite geometries are generated with Monte-Carlo technique and the composite conductivity is calculated with Finite Element Modeling (FEM) Traditional FEM strategies would give results resembling the ternary mixing equation, but when the CB particles are modeled as solid spheres whereas the CNT are modeled as solid cylinders surrounded by soft, conductive shells, the composite conductivity gained the same shape as observed experimentally. One possible interpretation is that a small geometrical rearrangement of the CNT fibers has a larger impact on the composite conductivity than a corresponding movement of the spherical CB particles. As a consequence, the CNT/CB/PMMA nanocomposite exhibits a special kind of synergy (“synergism”), caused by the grape-shaped morphology. These findings can be utilized in the future development and optimization of conductive polymer nanocomposites.
CRIS-Team Scopus Importer:2020-07-31
Keywords: conductivity; CPCs; simulation; ternary systems